Hospitalisations for sport-related concussions in US children aged 5 to 18 years during 2000–2004. Issue 8 (23rd January 2008) - Yang, J; Phillips, G; Xiang, H; Allareddy, V; Heiden, E; Peek-Asa, C
Abstract : Objectives: To describe patient and hospital characteristics associated with hospitalisation for a diagnosis of non-fatal sport-related concussion, and to determine factors associated with these hospitalisations. Methods: Children aged 5–18 years with a primary diagnosis of a sport-related concussion in the Nationwide Inpatient Sample (2000–2004) were identified. Length of stay and hospital charges for sport-related concussions were documented. Logistic regression was used to assess the association of patient or hospital characteristics with hospitalisations for sport-related concussion. Results: Between 2000 and 2004, a total of 755 non-fatal paediatric sport-related hospitalisations for concussion were identified. Nationwide, this represents 3712 hospitalisations and over US$29 million total hospital charges, with nearly US$6 million in total hospital charges per year. Over half (52.3%) of patients with concussion experienced loss of consciousness. Over 80% of the patients hospitalised for concussion received no procedures during their average 1.1 day (median 0.8 day) of hospital stay. Older age, but not gender, was associated with increased odds of sport-related hospitalisations for concussion. Non-teaching hospitals or hospitals in rural areas had significantly greater odds of admitting sport-related concussions versus other sport-related traumatic brain injuries compared with teaching or urban hospitals. Conclusions: Management of paediatric sport-related concussions varied, depending on the patient and the hospital. Better guidelines are needed for the identification and management of sport-related concussions. Standardised procedures for hospitals treating concussive injuries may also be warranted.